Analisis Perubahan Kebugaran Jasmani Siswa Saat dan Pasca Pandemi COVID-19 - Finsensius Mbabho; Muhammad Muhammad; Ismawandi Bripandika Putra; Angga Indra Kusuma; Yuni Fitriyah Ningsih (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aims to analyze the comparison of students' physical fitness during the COVID-19 pandemic and after the pandemic based on VO2 Max values. The research sample amounted to 100 students who had physical fitness data in two observation periods, namely during the pandemic and after the pandemic. Fitness measurements were carried out using the Beep Test (Multi-Stage Fitness Test / MSFT) to obtain a VO2 Max value. The results of the study showed that the average VO2 Max of students during the pandemic was 35 ml/kg/minute, while after the pandemic it increased to 42 ml/kg/minute. An increase of 7 ml/kg/min indicates a recovery in the student's aerobic capacity after returning to normal physical activity. Students who remained active in exercise during the pandemic showed better levels of fitness than students who did little physical activity. In addition, psychological factors, social support, and the availability of sports facilities also affect changes in students' physical fitness. Thus, the COVID-19 pandemic has been proven to have an impact on the decline in students' physical fitness, but these conditions can be restored through increased physical activity, environmental support, and structured physical education programs in the post-pandemic period.